Aesop's Fables: The Ant and the Grasshopper - Kelly, Miles (United Kingdom : Miles Kelly publishing Ltd, 2016)
PICTURE STORYBOOKS. The much-loved tale of The Ant and the Grasshopper has been beautifully captured by Barbara Vagnozzi's enchanting illustrations. Every page showcases delightful full-bled artwork, packed with charm and detail that will enthrall children aged 3+. The story has been simply retold to appeal to young readers and listeners alike.
Location: 3C
Keywords: Fiction book